THE ESTABLISHMENT OF AN EFFECTIVE MECHANISM IN THE ACTIVITIES OF THE PRESS OF THE KHOREZM REGION IN 1991-2024 (TAMADDUN NURI JURNALI, 2025)
The newspaper “Khwarezm truth” is one of the leading media covering the socio political life of the Khwarezm region. This newspaper has its rich history, activities today and plans for the future, reflecting on the effectiveness of the activities of our country after the years of independence, that it has a great reputation among the inhabitants of the region.